PEMBELAJARAN MENDALAM: PENGEMBANGAN MEDIA BERBASIS IS PRING SUITE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI GEOMETRI SISWA KELAS IV MIS TAHFIDZUL QUR'AN DARUN NAJAH - Zahara Br Karo; Effy Mulyasari; Andhin Dyas Fitriani; Ginda Rusit Hasibuan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Quality education is a key requirement for realizing a nation that is advanced, just, and prosperous. The deep learning approach has emerged as a new paradigm that emphasizes conceptual understanding and critical reflection in a learning process based on mindful, meaningful, and joyful learning. Skills in using information and communication technology (ICT) have become essential for educators in the 21st century. Geometry is one of the subjects that students find difficult to learn. This study aims to create an educational media product for fourth-grade elementary school geometry using the iSpring Suite software and integrating the application of the deep learning approach (DLA) based on the iSpring Suite software. The research and development (R&D) method used consists of five stages: analysis, design, development, implementation, and evaluation (ADDIE). The instruments included a subject matter expert questionnaire, a design expert questionnaire, a teaching practitioner questionnaire, and pre- and post-tests consisting of five essay questions administered to 24 students. The results of the study showed that the subject matter expert assessment scored 68.33% (Acceptable) and the design expert assessment scored 88% (Very Acceptable), while the teaching practitioner assessment scored 96% (Very Practical), and the presentation of student learning achievement reached 95% (Very Effective).